Rehabilitation as an opportunity for the evolution of the light weight facade. Case Study: the Architects’ Association of Catalonia - Carbonel Villanueva, José (2018)
Modern architecture is characterized by its flexibility and easy adaptation to changes. Light weight facades, thanks to the advantageous mutations that have appeared over the past years regarding building wraps, are an example of this. This essay will attempt to demonstrate that in the exercise of rehabilitating a modern facade it is possible to find ways that show the path of evolution. In 2014, 12 proposals made by architecture offices, mainly Catalan, were finalists of the contest for the rehabilitation facade of the Architects’ Association of Catalonia (COAC), a building that is located within the "Iberian DOCOMOMO Registry", which groups the most significant buildings of the Modern Movement of Spain and Portugal. This investigation will confront the proposals through the analysis of their improvements, grouped into four architectural aspects: technology, economics, socio-environmental concerns and formal concerns. These improvements are addressed through strategies, which by virtue of their recurrence will finally indicate the vectors of evolution for this case.